Local Degradation of PEDOT:PSS on Silicon Nanostructures Using Scanning Electrochemical Microscopy. Issue 10 (21st December 2022) - Dufil, Yannick; Dietrich, Marc; Zigah, Dodzi; Favier, Frederic; Sadki, Saïd; Gentile, Pascal; Fontaine, Olivier
Abstract: Conducting polymers show attractive characteristics as electrode materials for micro‐electrochemical energy storage (MEES). However, there is a lack of characterization techniques to study conjugated/conducting polymer‐based nanostructured electrodes. Here, scanning electrochemical microscopy (SECM) is introduced as a new technique for in situ characterization and acceleration of degradation processes of conducting polymers. Electrodes of PEDOT:PSS on flat silicon, silicon nanowires (SiNWs) and silicon nanotrees (SiNTrs) are analyzed by SECM in feedback mode with approach curves and chronoamperometry. The innovative degradation method using SECM reduces the time required to locally degrade polymer samples to a few thousand seconds, which is significantly shorter than the time usually required for such studies. The degradation rate is modeled using Comsol Multiphysics. The model provides an understanding of the phenomena that occur during degradation of the polymer electrode and describes them using a mathematical constant A 0 and a time constant τ. Abstract : Three silicon‐nanostructure‐PEDOT:PSS composite electrodes are rapidly and locally degraded by scanning electrochemical microscopy. Silicon nanowires stabilize the composite electrodes while nano‐shafts accelerate and emphasize the degradation effects. The role of native oxide formation on the nanostructures is put forward as the main hypothesis to explain the observed phenomena.